The impact of close surgical margins on recurrence in oral squamous cell carcinoma - Joseph Solomon; Ashley Hinther; T. Wayne Matthews; Steven C. Nakoneshny; Rob Hart; Joseph C. Dort; Shamir P. Chandarana (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Close margins influence treatment and outcome in patients with oral squamous cell carcinoma (OSCC). This study evaluates 187 cases of surgically treated OSCC regarding the impact of close margins on recurrence-free survival (RFS) and disease-specific survival (DSS). Methods Predictors of worsened outcome were identified using Kaplan-Meier analysis and multivariate Cox regression analysis. Results Tumour size [HR:1.70(0.95–3.08)], nodal status [HR:2.15(1.00–4.64)], presence of extracapsular spread (ECS) [HR:6.36(2.41–16.74)] and smoking history [HR:2.87(1.19–6.86)] were associated with worsened RFS. Similar factors were associated with worsened DSS. Close margins did not influence RFS or DSS. Conclusions While most conventional risk factors for OSCC conferred a worsened outcome, close margins did not. One explanation for this would be that close margins (< 5 mm) are equivalent to clear margins and the cutoff definition for a close margin should be re-evaluated. Lack of standardized pathology could also reduce accuracy of reporting of close surgical margins. Graphical abstract